Effect of curcumin on γ–ray-induced cell response. (11th January 2023) - Kostova, Nora; Staynova, Albena; Popova-Hadjiiska, Ljubomira; Georgieva, Dimka; Ivanova, Ilonka; Aneva, Nevena; Atanasova, Margarita; Hristova, Rositsa
Abstract: The purpose of the present study is to evaluate the effect of curcumin as a natural compound against radiation induced γ-foci and stable chromosome aberrations. Whole blood samples form three human volunteers were pretreated with curcumin at different concentrations (0.5, 10, 20 and 100 μg/ml). After 1-hour incubation, the lymphocytes were exposed to γ-rays (0.05, 0.5, 1 and 2 Gy). Radiation induced changes in cells were quantified using γ-H2AX/53BP1 assay and FISH analysis. Our results have shown that curcumin significantly reduced the frequency of both γ-foci and translocations. We found concentration-dependent increase of curcumin protective effect on γ-H2AX/53BP1 foci formation at all radiation doses. Concerning the translocations, after 0.05 and 0.5 Gy γ-rays the values of genomic frequencies are comparable within each dose and we did not observe any impact of curcumin. The most protective effect after 1 Gy exposure was found at 100 μg/ml curcumin. At 2 Gy irradiation, the maximum protection was achieved at 0.5 and 10 μg/ml of curcumin. Concentrations of 20 and 100 μg/ml also prevent lymphocytes but to less extent. Our in vitro study indicates radioprotective efficacy of curcumin against γ-ray induced damages in human lymphocytes. This observation suggests that curcumin may play a role to protect patients undergoing radiological procedures.